Critical analysis of Shyambazar traffic intersection area, Kolkata: A study of visual appropriateness - Das, Nibedita (Kansas State University, 2006)
This research explores the challenges related to the visual image of a city situated in a developing country. Originated as the colonial capital of British India, Kolkata faces new urban challenges in the post colonial world. This report intends to answer questions of imageability of the city as relevant to the Third World countries. Empathizing on the issues of scarcity of land, traffic congestion, accumulation of the urban poor, inadequacies in infrastructure and the organic expansion of fluid city boundaries under the neo-ideological globalization and liberal economic policies – Kolkata faces a host of urban problems. Imageability of the city usually tries to define the positive image of a city. The question here is, should the notions of imageability be confined to cities that inherently have succeeded in maintaining an appealing public image or should it be applied to the potential qualities of visual appropriateness to cities that have historically remained unattractive? This research intends to explore the visual quality of an area surrounding the five point intersection at Shyambazar, Kolkata, India. This study will be based on a number of observations and the different visual analysis techniques applicable in critically analyzing the visual conditions of an urban street pattern of a megacity in India. The main objective of this study is to find an appropriate visual quality for Kolkata, a megacity in the tropics – considering various related factors like – historical significance, demographic trends, geographical and climatological influences, transportation pattern, existing land use, socio-economic structure and inherent or associated urban problems of planning in developing nations.
Keywords: Kolkata, India; Visual study; Visual analysis; Traffic intersection; Urban and Regional Planning (0999)